1970
DOI: 10.2307/2036807
|View full text |Cite
|
Sign up to set email alerts
|

Nonoscillation Theorems for a Nonlinear Differential Equation

Abstract: Abstract.This paper is concerned with the problem of specifying growth conditions on the positive function q(t) which imply that all solutions of the nonlinear second order ordinary differential equation y" +q(t) | y \ ° sgn y = 0, a > 0, are nonoscillatory on a half line. Several different results are given, and the usual explicit monotonicity condition on q has been avoided to a certain degree.In the real, nonlinear differential equation (1) y' + î(0|y|"sgny = 0, C = d/dt), let q(t) be positive, continuous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Returning to (9), we deduce therefore that lim^^, t,l+xa\t) exists and is nonnegative. However, if such a limit is positive, then iMax(r) > e/t for some e > 0 and for all sufficiently large t, which would contradict assumption (5), proving (6). We now assume (7) holds.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Returning to (9), we deduce therefore that lim^^, t,l+xa\t) exists and is nonnegative. However, if such a limit is positive, then iMax(r) > e/t for some e > 0 and for all sufficiently large t, which would contradict assumption (5), proving (6). We now assume (7) holds.…”
mentioning
confidence: 84%
“…The function a(t) is said to be locally of bounded variation on [0, oo) if it is of bounded variation on each compact subinterval of [0, oo). If a(t) is continuous and locally of bounded variation on [0, oo), then a(t) admits the Jordan representation a(t) = a+(t) -a_(t) where a+, a_ are continuous nondecreasing functions of t. Gollwitzer [6] showed that the nonincreasing assumption on a(t) can be weakened to that of…”
mentioning
confidence: 99%
“…•'n°c da+(t) i s < oo, a(t) due to Gollwitzer [5]. Under this condition, he proved the following three nonoscillation criteria for (1):…”
mentioning
confidence: 94%
“…Equation (1) is said to be nonoscillatory if every solution has only a finite number of zeros. For details, we refer to [1,2,5,9].Since a(t) is assumed to be locally of bounded variation it admits a Jordan decomposition a(t) = a+(t) -a_(t), where a+ and a_ are continuous nondecreasing functions. A number of nonoscillation results for the nonlinear equation (1), y ¥= 1, require some sort of restriction on the growth of the function a(t), typically that a(t) be nonincreasing.…”
mentioning
confidence: 99%
See 1 more Smart Citation